EXTRUSION FORZADA: REPORTE DE UN CASO (2018)
The only possibility of treatment for the teeth with bad prognosis due to horizontal fractures, internal and/or external resorption below the level of the bone crest, subgingival tooth decay, extensive and isolated bony defects, are the extractions. Nevertheless, the forced extrusion becomes an alternative to treat these teeth. By means of a simple and safe dental movement it is managed to take the tooth to a plane in which its restoration is favored and the periodontal health is promoted. The purpose of this article is to report a case of dental force extrusion in a tooth with bad prognosis.